Performing barbers, surgeons and barber-surgeons in early modern English literature - Decamp, E (2011)
This study addresses the problem critics have faced in identifying contemporary perceptions of the barber, surgeon and barber-surgeon in early modernity by examining the literature, predominantly the drama, from the period. The name ‘barber-surgeon’ is not given formally to any character in extant early modern plays; only within the dialogue or during stage business is a character labelled the barber-surgeon. Barbers and surgeons are simultaneously separate and doubled-up characters. The differences and cross-pollinations between their practices play out across the literature and tell us not just about their cultural, civic and occupational histories but also about how we interpret patterns in language, onomastics, dramaturgy, materiality, acoustics and semiology. Accordingly, the argument in this study is structured thematically and focuses on the elements of performance, moving from discussions of names to discussions of settings and props, disguises, stage directions and semiotics, and from sound effects and music, to voices and rhetorical turns. In doing so, it questions what it means in early modernity to have a developed literary identity, or be deprived of one. The barber-surgeon is a trope in early modern literature because he has a tangible social impact and an historical meaning derived from his barbery and surgery roots, and consequently a richly allusive idiom which exerted attraction for audiences. But the figure of the barber-surgeon can also be a trope in investigating how representation works. An aesthetic of doubleness, which this study finds to be diversely constructed, prevails in barbers, surgeons’ and barber-surgeons’ literary conception, and the barber-surgeon in the popular imagination is created from opposing cultural stereotypes. The literature from the period demonstrates why a guild union of barbers and surgeons was never harmonious: they are opposing dramaturgical as well as medical figures. This study has a wide-ranging literary corpus, including early modern play texts, ballads, pamphlets, guild records, dictionaries, inventories, medical treatises and archaeological material, and contributes to the critical endeavours of the medical humanities, cultural materialists, theatre historians and linguists.